Origin of the giant persistent photoconductivity in LaAlO3/SrTiO3 heterostructures probed by noise spectroscopy. (20th February 2023) - Eom, Kitae; Lee, Jung-Woo; Yang, Gyeongmo; Kim, Youngmin; Jeon, Jaeyoung; Yeon, Jieun; Lee, Hyungwoo
Highlights: The origin of the giant persistent photoconductivity in LaAlO3 /SrTiO3 heterostructures is explained by the photo-induced valence change in oxygen vacancies. The change in the ionization state distribution is successfully probed by the noise spectroscopy technique. The noise spectra correlate the ionization state distribution and the charge trapping behavior of oxygen vacancies. The neutralization of the ionized oxygen vacancies near the LaAlO3 /SrTiO3 interface hinders the fast and complete charge relaxation, resulting in the strong persistent photoconductivity. Abstract: LaAlO3 /SrTiO3 (LAO/STO) heterostructures have shown a strong persistent photoconductivity (PPC) at room temperature. The abnormally strong PPC has attracted immense research interest due to its possible applications in optically-tunable electronic devices. Despite its promise, the fundamental understanding of the PPC in the LAO/STO heterostructures is still elusive. Herein, we report that the giant PPC originates from the photo-induced valence change in oxygen vacancies near the LAO/STO interface. Our spectral analysis of the photocurrent and the model-fitting study consistently show that the ionized oxygen vacancies near the interface are neutralized during the electron relaxation process. They hinder the complete relaxation of the photoexcited electrons by the deeply-located oxygen vacancies and result in the strong PPC. The change in the ionization state distribution of the oxygen vacancies is probed by the persistent noise behavior at the frequency between 1 kHz and 20 kHz regime. These results provide insight into the role of oxygen vacancies in influencing the internal charge distribution and triggering the PPC phenomena in complex oxide heterostructures. Graphical abstract: Image, graphical abstract